Defective APETALA2 Genes Lead to Sepal Modification in Brassica Crops - Zhang, Yanfeng; Huang, Shuhua; Wang, Xuefang; Liu, Jianwei; Guo, Xupeng; Mu, Jianxin; Tian, Jianhua; Wang, Xiaofeng (Frontiers in Plant Science, 2018)
Many vegetable and oilseed crops belong to Brassica species. The seed production of these crops is hampered often by abnormal floral organs, especially under the conditions of abiotic conditions. However, the molecular reasons for these abnormal floral organs remains poorly understood. Here, we report a novel pistil-like flower mutant of Brassica rapa. In the flower of this mutant, the four sepals are modified to one merged carpel that look like a ring in the sepal positions, enveloping some abnormal stamens and a pistil, and resulting in poor seed production. This novel mutant is named sepal-carpel modification (scm). DNA sequencing showed that the BrAP2a gene, the ortholog of Arabidopsis APETALA2 (AP2) that specifies sepal identity, losses the function of in scm mutant due to a AP2a a 119-bp repeated sequence insertion that resulted in an early transcription termination. BrAP2b, the paralog of BrAP2a featured two single-nucleotide substitutions that cause a single amino acid substitution in the highly conserved acidic serine-rich transcriptional activation domain. Each of the two BrAP2 genes rescues the sepal defective phenotype of the ap2-5 mutant of Arabidopsis. Furthermore, the knockout mutation of the corresponding BnAP2 genes of oilseed rape (B. napus) by CRISPR/Cas9-mediated genome editing system resulted in scm-like phenotype. These results suggest that BrAP2 gene plays a key role in sepal modification. Our finding provides an insight into molecular mechanism underlying morphological modification of floral organs and is useful for genetic manipulation of flower modification and improvement of seed production of Brassica crops.